1976
DOI: 10.1172/jci108377
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, blood transport, and degradation of antidiuretic hormone in man.

Abstract: A BS TR A CT The distribution, blood transport, and metabolic clearance of physiological concentrations of antidiuretic hormone were studied in 10 hydrated normal subjects with radioiodinated arginine vasopressin ('25I-AVP). At 370C no binding of '"I-AVP to plasma proteins could be demonstrated, but some metabolites were associated with plasma proteins. "I-AVP was rapidly distributed into a space approximating the extracellular fluid volume. Metabolic breakdown products became demonstrable within minutes after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
89
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(90 citation statements)
references
References 27 publications
(29 reference statements)
0
89
0
1
Order By: Relevance
“…The fact that there are only limited data on AVP in ADPKD may be because AVP is difficult to measure due to its small size, binding to platelets, and very short ex vivo t 1/2 (27,28). An assay was recently developed to measure copeptin (29).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that there are only limited data on AVP in ADPKD may be because AVP is difficult to measure due to its small size, binding to platelets, and very short ex vivo t 1/2 (27,28). An assay was recently developed to measure copeptin (29).…”
Section: Discussionmentioning
confidence: 99%
“…14 One problem in the determination of the activity of vasopressin during a field study is its short half life time of 24.1 min. 26 Considering that the athletes got slower and slower during the race, the activity of vasopressin will also be reduced. The fastest Ironman was on Day 1, the slowest Ironman was on Day 9.…”
Section: Discussionmentioning
confidence: 99%
“…1992) suggesting that the kidney is responsible for about half of all clearance. A study in healthy humans with radioiodinated AVP reported renal clearance of 80聽mL/min (half鈥恡ime 24聽min), with 27% of total due to the kidney (Baumann and Dingman 1976). Previous work has demonstrated that I 125 鈥怉VP has a slower total clearance from circulation with a half鈥恡ime of 28聽min, indicating that the human study may be underestimating renal clearance.…”
Section: Curve Fittingmentioning
confidence: 99%